PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN DAN DANA PIHAK KETIGA PADA PROFITABILITAS - Primadewi, Cok Istri Dian Rini; Suputra, I Dewa Gde Dharma (E-Jurnal Akuntansi, 2015)
Bank important it’s the institutiones acts as of financialy intermedediary betweened havee a fundss which required funding. Regional Development Bank (BPD) Bali is a special area banks running the local economy by offering savings and loans to customers. My reaserched examiness so it’s effecct capital adequacy ratio, non-performing loans and deposits on profitability in BPD Bali. The data used include the financial statements and annual reports BPD Bali during the period 2005 - 2012. The sampling technique using saturated sample, so that the population used all customers of BPD Bali. Based on the analysis of the results obtained capital adequacy ratio (CAR) has positive effect on profitability BPD Bali, non-performing loan (NPL) and the negative impact of third party funds have negative effect on the profitability of BPD Bali. Keyword : ratio, BPD Bali, profitability